Кашуби: дорога з небуття - Сегеда, О. (Народна творчість та етнографія, 2009)
The author considers the problems relating to investigation of the lifestyle of Kashubs – an ethnographic group of the Slavic nations, which preserves its material and spiritual culture’s originality and realises the necessity of conservation of the traditions.